2020
DOI: 10.1177/0264619620972147
|View full text |Cite
|
Sign up to set email alerts
|

Practices and perceptions of German itinerant teachers in the field of visual impairment: Exploratory research focussing on three types of itinerant services

Abstract: This study aimed to clarify the practices and perceptions of itinerant teachers of students with visual impairments (TVIs) in inclusive education following three different types (i.e., school-based, school-based single role, and centre-based), identifying the salient factors that enable them to fulfil their roles. To date, the majority of the existing research has focussed on centre-based itinerant TVIs, with scant attention paid to the other itinerant types. This study mitigates this lack of research. Designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(30 reference statements)
2
1
0
Order By: Relevance
“…The participants in this study reported several challenging aspects of being an itinerant during the pandemic. They echoed similar concerns described in the study by Miyauchi and Gewinn (2021) that aimed to clarify the practices and perceptions of TVIs. Time management, flexibility, open-mindedness, and interpersonal skills that were identified by Miyauchi and Gewinn (2021) as important training needs for TVIs before the pandemic were reportedly described as essential during the pandemic by the participants in this study.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The participants in this study reported several challenging aspects of being an itinerant during the pandemic. They echoed similar concerns described in the study by Miyauchi and Gewinn (2021) that aimed to clarify the practices and perceptions of TVIs. Time management, flexibility, open-mindedness, and interpersonal skills that were identified by Miyauchi and Gewinn (2021) as important training needs for TVIs before the pandemic were reportedly described as essential during the pandemic by the participants in this study.…”
Section: Discussionsupporting
confidence: 63%
“…They echoed similar concerns described in the study by Miyauchi and Gewinn (2021) that aimed to clarify the practices and perceptions of TVIs. Time management, flexibility, open-mindedness, and interpersonal skills that were identified by Miyauchi and Gewinn (2021) as important training needs for TVIs before the pandemic were reportedly described as essential during the pandemic by the participants in this study. Moreover, the findings of this study suggest that the significance of being affiliated with other educators in the state gave itinerant TVIs and COMS not only a sense of security and safety but also reaffirmed that they were not working alone during the uncertain and rapidly changing times of the pandemic.…”
Section: Discussionsupporting
confidence: 63%
“…According to the purpose of the research, there are different types of research that help to make research study more effective. The exploratory research type is followed in this study to evaluate the influence of music in changing the cultural values in society [3]. The exploratory research type enables researchers to explore every aspect of the study to improve the effectiveness of the research.…”
Section: Research Typementioning
confidence: 99%